(3MGTjI bhd CMeOjIs - (3GdYeQj GdMfaj, CHh GdYHGS, GHf GdNVQ, bhd CMeO (B- (3TgGH GdOjf, CMeO Hf eMeO Hf YeQ Hf eSde, (B785 (3g`s
(3ChdgG (B:s
(3MeOG dc Ydi eG efMJ Hg ef eYGQa GdCaGVd adeG cGfJ GdahGFO GdafGQjI Ydi eG dG Yf GdZehV hGdEZdGb heY gPG ENhGf GdReGf QGZHhf ajgG ZGjI QZHI hGTJjGb YdbJ YdjgG eG jcTa GdZdGb hjRj GdZehV MJi jJjSQ dge s
(3BNQgG (B:s
(3hEf UM Pdc hEfeG CaQOgG HGdPcQ eY GfOQGLgG aj GdbVGjG dCfge cGfhG jLYdhf GdCMcGe aj HGH ebGHd dHGH ddbVGjG hdeG LeYgG gjFgG ddefGSHI CQGO GdJfHjg Ydi Pdc ade jcJaj HPcQ GdbVGjG eY TehdgG ddCMcGe JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1/225s
(3GdCYdGe (B1/225s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs